2016
DOI: 10.1039/c5sm02938d
|View full text |Cite
|
Sign up to set email alerts
|

Tuning protein mechanics through an ionic cluster graft from an extremophilic protein

Abstract: Proteins from extremophilic organisms provide excellent model systems to determine the role of non-covalent interactions in defining protein stability and dynamics as well as being attractive targets for the development of robust biomaterials. Hyperthermophilic proteins have a prevalence of salt bridges, relative to their mesophilic homologues, which are thought to be important for enhanced thermal stability. However, the impact of salt bridges on the mechanical properties of proteins is far from understood. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(44 citation statements)
references
References 78 publications
1
43
0
Order By: Relevance
“…For that reason, mechanical properties of cold shock proteins have been extensively studied both experimentally and in simulations. 33,[52][53][54][55] Moreover, the unfolding of CspA under force and high temperature was previously investigated by our group using all-atom simulations, 33 provinding an interesting reference for the present work.…”
Section: Systemmentioning
confidence: 93%
“…For that reason, mechanical properties of cold shock proteins have been extensively studied both experimentally and in simulations. 33,[52][53][54][55] Moreover, the unfolding of CspA under force and high temperature was previously investigated by our group using all-atom simulations, 33 provinding an interesting reference for the present work.…”
Section: Systemmentioning
confidence: 93%
“…Polyproteins were constructed using a method which makes use of Gibson assembly cloning and purified using a method described previously, including an additional stage to remove any bound nucleic acid . Three (His) 6 -tagged chimeric polyprotein constructs, each containing four domains of I27 interdigitated with three domains of a CSP, were produced: (i) a polyprotein containing the wild-type CSP from the hyperthermophilic organism T.…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescence spectra were measured in a 1 cm path length quartz cuvette using an excitation wavelength of 280 nm and emission range of 320–380 nm with a 1 nm step size. Unfolding transitions were followed by a change in the barycentric median (BCM) as described previously. , The BCM “center of mass” of each spectrum between 320 and 380 nm was calculated, where I (λ) is the fluorescence value at a respective wavelength. The BCM value for each spectrum was plotted against temperature ( T ) or denaturant concentration ([GdnHCl]), and the unfolding transition was followed by an increase in BCM due to a shift to a higher wavelength of the unfolded peak.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent example, we demonstrated that a protein from a hyperthermophilic organism can be used to determine the role of salt bridge interactions in determining protein stability [238]. SMFS experiments showed that at ambient temperatures TmCsp is mechanically stronger yet, counter-intuitively, its native state can withstand greater deformation before unfolding (i.e.…”
Section: Lessons From Extreomophiles: Smfs Studies Of Extreme-loving mentioning
confidence: 99%